I. Report on sugar-cane borers at Soledad, Cuba, and II. Dry-season studies of cane homptera at Soledad, Cuba : with a list of the coccids of the districtTT - - Salt, George W. (1903-2003) (Harvard University Press, 1926)
Contributions from the Harvard Institute for tropical Biology and Medecine, III